2019
DOI: 10.1021/acsanm.9b00757
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-Dependent Degradation of 11 Types of Carbon Nanotubes: Safety Implications

Abstract: Understanding the biodegradation profiles of various types of carbon nanotubes (CNTs) is important for their safe use according to their structural characteristics. To investigate the relationship between the biodegradation and the physicochemical properties of CNTs, sodium hypochlorite was used to degrade CNTs because it is believed to be a key oxidizer of CNTs inside macrophages and neutrophils. The complete degradation of CNTs in response to sodium hypochlorite was confirmed, and the half-lives of 11 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…The changes in the amounts of SG-CNTs after treatment with NaClO under different conditions was estimated by measuring the optical absorbance of CNT dispersions at a wavelength of 700 nm at each time point using a Lambda 1050 ultraviolet/visible light/near infrared (UV/vis/NIR) spectrometer (Perkin Elmer, Waltham, MA, USA) as reported previously [ 29 , 31 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the amounts of SG-CNTs after treatment with NaClO under different conditions was estimated by measuring the optical absorbance of CNT dispersions at a wavelength of 700 nm at each time point using a Lambda 1050 ultraviolet/visible light/near infrared (UV/vis/NIR) spectrometer (Perkin Elmer, Waltham, MA, USA) as reported previously [ 29 , 31 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the degradation rates of the eleven investigated types of CNTs are different, their degradation trends are the same. The degradation rates of CNTs with NaClO mainly depend on the diameters of the different types of CNTs, ordered SWNTs ≥ CNHs > thinner MWNTs > thicker MWNTs [ 31 ], and two-dimensional graphene oxide sheets degrade faster than one-dimensional oxidized CNTs [ 32 ]. However, for practical industrial applications, more fundamental research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we believe that a subacute study by intraperitoneal injection with a four week observation predicts the carcinogenicity of the bio-persistent fibrous material, such as asbestos and MWCNT [ 117 , 118 ]. Commercial chlorine bleach can degrade MWCNT to CO 2 ex vivo, which would facilitate the disposal of this nanomaterial [ 138 ].…”
Section: Association Of Cutting-edge Engineering and Cancermentioning
confidence: 99%
“…Because hypochlorite generated by enzymatic reactions is a key oxidizer of CNTs inside of macrophages or neutrophils (Vlasova et al, 2011(Vlasova et al, , 2012, Zhang et al used sodium hypochlorite to investigate the biodegradation features of 11 types of commercially available CNTs. They found that degradation of CNTs was generally diameter-or thickness-dependent, with the degradation rates following the order SWCNTs ≥ CNHs > thin MWCNTs > thick MWCNTs (Zhang et al, 2019).…”
Section: Cnt Types and Lengthsmentioning
confidence: 99%
“…In addition to the aforementioned factors, many other parameters could influence the biodegradability of CNTs in living systems, such as dispersion states of the CNTs (Zhang et al, 2019), cell types (Kagan et al, 2010;Yang et al, 2019), uptake of CNT and immune recognition (Turabekova et al, 2014;Mukherjee et al, 2018;Zhang et al, 2018). In addition, the biodegradability of CNTs is likely to be affected by a combination of multiple factors rather than by a single factor.…”
Section: Other Factorsmentioning
confidence: 99%